Conhecimento pedagógico do conteúdo em Botânica: desafios para a formação na Educação Básica - Pes, Cinara Dal Santo (2019)
This study is part of the research line Teacher Training of the Graduate Program in Teaching Science and Mathematics, at the Franciscan University and aims to analyze how teachers of Basic Education manifest the Pedagogical Knowledge of Content in Botany. This curricular component was chosen, as well as the specific content for study - Angiosperms (Kingdom Plantae), based on researches already carried out in elementary and high school, as they are subjects of biology that present difficulties in the teaching and learning process. To characterize the teacher's knowledge base, especially the pedagogical content knowledge (PCK), the model proposed by Lee Shulman (1986, 1987) was employed. The methodological approach of this study was qualitative, conducted with teachers who teach the sixth grade of elementary school and the third year of high school, in state public schools located in the city of São Luiz Gonzaga, Rio Grande do Sul, duly authorized by the 32nd. Education Coordination. The data were obtained through questionnaires, analysis of official documents, pedagogical training, logbook, filming and an instrument to characterize pedagogical content knowledge, a tool called content representation - CoRe (adapted from LOUGHRAN; BERRY; MULHALL, 2004). The CoRe consists of a set of eight questions directed to the teacher about teaching a specific content, in the case of this study, related to the teaching of the theme Angiosperms (Kingdom Plantae). From the interpretation of the data was possible to know the profile of the teachers involved in the teaching of botany in basic education; verify how teachers direct their teaching performance, in view of the PCK; find out how botany is prescribed in official documents; identify teacher concerns related to PCK; diagnose the professional difficulties of science / biology teachers related to botany; contribute to the process of continuing education of Science / Biology teachers, through pedagogical training, emphasizing the Pedagogical Knowledge of Content in Botany. It was found that the teachers participating in the research, in general, have the domain of Pedagogical Knowledge, but not of Content Knowledge in Botany, a fact that offers limitations for the structuring of Pedagogical Content Knowledge and good conduct of the teaching and learning process.